The Role of Broadcasting in Cultural Preservation: A Comparison of SMTV and Radio Barani - Puspitasari, Euis Evi; Tabroni, Roni; Rizkya Hantoro, Naditha; Sutiandi (Komunikator, 2026)
This study examines the role of broadcasting institutions in preserving local culture in the era of digital media convergence, using a comparative analysis of SMTV Sumedang and Radio Barani Bandung in West Java. The background of this research stems from the declining visibility of regional arts, languages, and traditions amid the dominance of popular content, while local media must remain technologically adaptable and institutionally resilient. Local broadcasting institutions occupy a strategic position because they function not only as information channels but also as custodians of community cultural identity. This research analyzes the institutional orientations, broadcast program strategies, human resource management practices, and digital adaptation strategies of the two institutions. The findings identify two distinct models of cultural preservation. Radio Barani represents a community-idealism model that emphasizes cultural authenticity through traditional broadcasting and community-driven live streaming, whereas SMTV reflects an industry-adaptive model characterized by professional management and cross-platform distribution of short-form digital content. The study shows how these two types of broadcasting institutions negotiate the tension between cultural preservation and the demands of media convergence within different institutional contexts. Theoretically, this study contributes to communication and broadcasting scholarship by proposing a comparative dual-model framework of local cultural preservation in convergent media environments. The findings highlight that community-based and industry-based broadcasters develop divergent yet complementary strategies to sustain local cultural identity in the digital era.